Cell proliferation and carcinogenesis: an approach to screening for potential human carcinogens - Cohen, Samuel M. (Frontiers in Oncology, 2024)
Cancer arises from multiple genetic errors occurring in a single stem cell (clonality). Every time DNA replicates, mistakes occur. Thus, agents can increase the risk of cancer either by directly damaging DNA (DNA reactive carcinogens) or increase the number of DNA replications (increased cell proliferation). Increased cell proliferation can be achieved either by direct mitogenesis or cytotoxicity with regenerative proliferation. Human carcinogens have a mode of action of DNA reactivity, immunomodulation (mostly immunosuppression), increased estrogenic activity (mitogenesis), or cytotoxicity and regeneration. By focusing on screening for these four effects, utilizing in silico, in vitro, and short-term in vivo assays, a biologically based screening for human chemical carcinogens can be accomplished with greater predictivity than the traditional 2-year bioassay with considerably less cost, less time, and the use of fewer animals.